Taxonomic notes of the Cucujus costatus Species-group, with description of a new species from Yunnan, China (Coleoptera, Cucujidae) - Jiang, Ri-Xin; Chen, Xiang-Sheng (Zootaxa, 2025)
The genus Cucujus Fabricius, 1775 is widely distributed throughout the Holarctic region, and contains 28 species and three subspecies with 16 species and two subspecies of them are recorded in China. In the present paper, we describe an extraordinary new species, Cucujus zhengyucheni sp. nov., which has three distinct longitudinal carinae on each elytron, a character only appears on C. costatus Zhao & Zhang, 2019, also from China. Moreover, the spermatheca of female C. costatus is provided for the first time, and both close species are well compared by the genitalia of both sexes.